Global prevalence of excessive daytime sleepiness in patients with obstructive sleep apnea: a systematic review and meta-analysis - Salari, Nader; Gholami, Amin; Jalili, Framarz; Zereshki, Ehsan; Heidarian,, Pegah; Shohaimi, Shamarina; Mohammadi, Masoud (Association of Otolaryngologists of India, 2024)
The prevalence of obstructive sleep apnea (OSA) has increased worldwide in recent years, becoming a significant public health concern. One of the most important complications experienced by individuals with OSA is excessive daytime sleepiness (EDS). This study aims to investigate the prevalence of EDS in patients with OSA through a systematic review and meta-analysis. Electronic databases including PubMed, Scopus, Web of Science, Embase, ScienceDirect, and the Google Scholar search engine were systematically searched for studies investigating the prevalence of EDS in people with OSA up to December 2023. Data analysis was conducted using Comprehensive Meta-Analysis software (Version 2), employing a random effects model. The heterogeneity of the studies was assessed using the I² index. In review of 15 studies with a combined sample size of 42,924 individuals found that the global prevalence of EDS in patients with OSA was 39.9% (95% CI: 34.4–45.7). The regression results indicated that as the sample size increased, the prevalence of EDS in patients with OSA decreased (p < 0.05). Additionally, an increase in the years of the studies conducted was associated with a decrease in the prevalence of EDS in patients with OSA, although this trend was not statistically significant (p = 0.856). Based on the results of this study, the global prevalence of EDS in patients with OSA is significant. Given the increasing prevalence of OSA, it is crucial for health decisionmakers to recognize the importance of this issue, raise public awareness, and address the dangerous effects of EDS on the population.